Niveles de ansiedad prequirúrgica en pacientes que van a ser intervenidos en colecistectomía laparoscópica programada, histeroctomía y prostatectomía en el Hospital Manuel Ygnacio Monteros IESS de la ciudad de Loja en el periodo noviembre 2014-marzo 2015 - Monteros Carreño, Ehinsteen Leonardo (2015)
This research was conducted to determine the levels of preoperative anxiety and anxiety response system most used in patients who underwent surgery in Scheduled Laparoscopic Cholecystectomy, Hysterectomy and Prostatectomy. It´s execution was performed at the Manuel Ygnacio Monteros Hospital in the city of Loja, with patients who were previously diagnosed and subsequently their programmed surgery. The research is quantitative, descriptive and cross-cutting as it is confined within a specific time slot and the results were measurable and represented numerically. The Hamilton Anxiety Scale and The Inventory of Situations and Responses "ISRA" were applied. Using the methodology and instruments I found that 83% of the evaluated patients presented some level of anxiety, this being a very important risk factor in the surgical process and subsequent recovery. At the same time it was evidenced that the response system more prevalent is the cognitive anxiety marked with 60%. Hysterectomy surgery showed the highest level of anxiety, moderate anxiety with 53%, in surgical procedures evaluated. The results have generated recommendations such as psychological preparation to preoperative patient to prevent anxious-depressive factors which might contribute negatively on the psyche of the individual and their subsequent recovery. Keywords: preoperative anxiety, anxiety levels, response system anxiety, cognitive anxiety, psychological preparation.